The influence of organizational commitment, job satisfaction, and organizational culture on employee performance in the forestry service of north sumatra province - Yanti Hasibuan Hasibuan; KRT Hardi Mulyono K.Surbakti; Muhammad Hilman Fikri Fikri (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the effect of Organizational Commitment, Job Satisfaction and Organizational Culture on Employee Performance at the North Sumatra Provincial Forestry Service either partially or simultaneously. This type of research uses primary data and secondary data. Meanwhile, data collection techniques used observation, questionnaires, and interviews. The population of North Sumatra Province Forest Service employees was 147 employees. The samples for North Sumatra provincial forestry service employees were 60 respondents. Data analysis techniques used multiple linear regression analysis, hypothesis testing (t-test and F-test), and the coefficient of determination. The results of this study prove that partially known t-count Organizational Commitment (X1) of 2,622 > 1,672, Job Satisfaction (X2) of 2,520 > 1,672, and Organizational Culture (X3) of 2,794 > 1,672, then H0 is rejected and Ha is accepted, which means has an effect on employee performance, and simultaneously it is known that the F-count value is 17,537> F-table 2.77, so there is an influence of organizational commitment, job satisfaction and organizational culture on employee performance at the Forest Service of North Sumatra Province